La inestabilidad laboral de mujeres gestantes o lactantes en Ecuador representa una vulneración de derechos fundamentales - Espinoza Contento, Miguel Santiago (2025)
The research on job instability among pregnant or breastfeeding women in Ecuador highlights a violation of fundamental rights. Its objective is to analyze the effectiveness of Ecuadorian regulations on job stability for pregnant or breastfeeding women, considering their practical application and judicial enforcement, to propose reforms that guarantee real and effective protection of these rights. The research was conducted using the Inductive-Deductive method, which started from a specific context based on the LOSEP regarding rights, violations, and job permanence of pregnant or breastfeeding women, as well as other principles established in the Constitution of the Republic of Ecuador, which guarantees the rights to work, equality, and non-discrimination. Additionally, the Analytical-Synthetic method was used to examine the evidence related to job instability, and the Documentary method helped identify the arguments that support the issue by analyzing laws, regulations, and principles that highlight discriminatory practices. The analysis of Ruling 2903-19-EP/24 from the Constitutional Court of Ecuador addresses reinforced labor protection and the right to care for pregnant or breastfeeding women with provisional appointments. In this case, the claimant filed an extraordinary protection action against a ruling by the Provincial Court of Justice of Pichincha, which had annulled a previously granted protection action. The research concludes that there is a lack of judicial oversight regarding the enforcement of regulations on job stability for pregnant or breastfeeding women, leading to the persistence of discriminatory practices. Therefore, it is recommended to establish monitoring mechanisms, such as labor audits, to identify and report non-compliance with labor regulations to the relevant authorities.